Unemployment in the Carpatho-Podilsky Region of the Ukraine - Kilinskaya, Klavdya; Lopushnyak, Liubomyr (Journal of Education, Health and Sport, 2018)
The presented publication analyses unemployment and employment processes in the context of administrative regions of the Carpatho-Podilsky region of the Ukraine. The issues of economic activity of the population, types of appeals of local population to employment services, age structure of employment, level of employment, regional labour services, employment of population by sex-age structure are highlighted.